The Integration of Islamic Values and Banjarese Culture in Bahalarat al-Qur’an Tradition, South Kalimantan - Riza Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study explores the bahalarat al-Qur’an tradition among the Banjar people of South Kalimantan as an expression of cultural integration between Islamic ethics and local values. Using a phenomenological qualitative approach framed by Durkheim’s theory of cultural integration, the research investigates how reverence and repentance toward the Qur’an are practiced through communal rituals. Data were obtained through observation, interviews, and documentation involving religious leaders, elders, and families. Findings reveal that bahalarat al-Qur’an functions as (1) a moral-spiritual mechanism to restore the Qur’an’s sanctity, (2) a communal ritual fostering social cohesion, (3) a pedagogical medium transmitting adab (etiquette) and moral responsibility, and (4) an adaptive tradition that evolves from collective to personal practice across generations. The tradition demonstrates how Islamic values of ta‘zhim (reverence) and istighfar (repentance) are localized within Banjar culture, transforming unintentional errors into moral learning and social solidarity.